Analisis Modernisasi dalam Tradisi Berinai Curi di Desa Keban Agung Kecamatan Air Periukan Kabupaten Seluma - Nasution, Egi Alfina Julius (IJOCE: Indonesia Journal of Civic Education, 2026)
This study discusses the Berinai Curi tradition, a series of wedding customs in Keban Agung Village, Air Periukan District, Seluma Regency, which is rich in cultural, social, and religious values ​​and has been passed down from generation to generation. The study used a qualitative method with a descriptive approach, with data obtained through in-depth interviews, observation, and documentation with traditional leaders and the local community. The results of the study indicate that modernization influences the Berinai Curi tradition through the use of technology in event preparation, community lifestyles that impact social values, and the reduction of symbolic meanings that were once highly respected. Nevertheless, the people of Keban Agung Village continue to strive to preserve this tradition as a local cultural identity by adapting to current developments, so that the Berinai Curi tradition can still be maintained even though in a simpler form.   Keywords: Modernization, Tradition, Berinai Curi, Keban Agung, Seluma